A Collaborative Based Academic Supervision Model for Enhancing Teacher Performance - Widiyanti, Widiyanti; Harris, Taufiq; Faizin, A. (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to describe the implementation of collaborative-based academic supervision integrated with a clinical approach in improving teacher performance at the elementary school level. The research method employed is a descriptive qualitative approach, focusing on the processes of supervision planning, classroom observation, post-observation reflective dialogue, and collaborative follow-up actions. The findings indicate that collaboratively conducted academic supervision contributes to improved teacher performance, particularly in lesson planning, instructional implementation, and teachers’ professional attitudes. This study proposes a more adaptive supervision model grounded in professional learning.